The Independent Curriculum Approach in Supporting Independent Learning for Inclusive Students in Elementary Schools - Citrawati, Tyasmiarni (Widyagogik, 2024)
This study aims to examine how the Merdeka Curriculum supports independent learning for inclusive students in elementary schools. The method used is qualitative research with a case study approach in several elementary schools that have implemented the Merdeka Curriculum. Data were collected through observations, interviews, and document analysis. The results of the study show that the Merdeka Curriculum has a positive impact on the independent learning of inclusive students through an adaptive and responsive approach to student needs. The discussion indicates that the freedom to choose learning materials and methods, as well as the role of adaptive teachers, significantly influences the increase in student independence. The conclusion of this study is that the Merdeka Curriculum is effective in supporting the independent learning of inclusive students in elementary schools, which in turn can enhance their academic achievement and social skills.